Testosterone precursors: Use and abuse in pediatric athletes - Smurawa, T. M.; Congeni, J. A. (Pediatric Clinics of North America, 2007)
The dietary supplements androstenedione, dehydroepiandrosterone, and androstenediol are precursors in the endogenous production of testosterone. The efficacy and safety of these prohormones are not well established but are promoted to have the same androgenic effects on building muscle mass and strength as anabolic-androgenic steroids. Studies have demonstrated repeatedly that acute and long-term administration of these oral testosterone precursors does not effectively increase serum testosterone levels and fails to produce any significant changes in lean body mass, muscle strength, or performance improvement compared with placebo. The Anabolic Steroid Control Act of 2004 lists androstenedione as a schedule III controlled substance, and it is regulated by the U.S. Food and Drug Administration. Testosterone precursors are banned by most major sports organizations.